(untitled) (Research, Society and Development, 2021)
Temporomandibular joint ankylosis is still a subject in evidence in the literature, being the focus of several divergences of opinion, mainly regarding etiology and treatment. Based on this, this study aims to present a systematic review on the subject illustrated through a clinical case report of bilateral TMJ ankylosis that occurred as a sequela of radiotherapy used in the treatment of an auditory tube lymphoepithelioma. In the reported case, bilateral ankylosis of the TMJ progressively occurred for 20 years. This condition was treated with surgical removal of ankylosis and installation of bilateral custom prosthesis. In the systematic literature review, the most commonly referred etiology was trauma, representing the vast majority with 1185 cases, followed by 110 cases of infection, 1 of jaw choronoid process hyperplasia, 102 idiopathic, 17 congenital, 10 systemic problems (such as osteoarthritis and spondylitis) and 18 by previous surgery. Radiotherapy as an etiologic factor for TMJ ankylosis should be taken into account and studies that suggest specific prevention protocols should be performed.